PERANCANGAN BALANCED SCORECARD SEBAGAI ALAT UNTUK REVIEW STRATEGI PERUSAHAAN (STUDI KASUS PADA PT â€œSBPâ€ DI SURABAYA) - FEBRINA, MARIA (Universitas Katolik Widya Mandala Surabaya, 2012)
Traditional systems are considered no longer relevant because it only focuses on the financial side of it which only reflects past performance and is not capable of providing accurate information about the circumstances experienced by the company at the time. Business entities who want to stay in the competition, should consider also the non-financial. Or in other words, companies should pay attention to balance and integration between these two aspects. Balanced Scorecard measures the performance of four different perspectives namely: customer perspective, internal business process perspective, learning and growth perspective, as well as financial perspective. The Balanced Scorecard also related to the critical success factors of business entities, which can be used to determine how large the contribution of each non-financial perspectives of the financial perspective, to determine how the perspectives which require special attention from companies in order to help companies prepare themselves to face competition that sooner or later it will happen. Balanced Scorecard translating promising strategy into strategic objectives of a comprehensive, coherent, balanced, and scalable, and can facilitate the coordination of various strategic goals through communication, persuasion, and trust among the personnel of the organization. PT